2002
DOI: 10.1097/00004647-200208000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Akt Activity is Associated with Activation of Forkhead Transcription Factor after Transient Forebrain Ischemia in Gerbil Hippocampus

Abstract: Summary:The authors recently reported that sodium orthovanadate rescues cells from delayed neuronal death in gerbil hippocampus after transient forebrain ischemia through phosphatidylinositol 3-kinase-protein kinase B (Akt) pathway ). In the current study, they demonstrated that the activation of FKHR, a Forkhead transcription factor and a substrate for Akt, preceded delayed neuronal death in CA1 regions after transient forebrain ischemia. Adult Mongolian gerbils were subjected to 5-minute forebrain ischemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…Our findings extend work showing that brain injury activates FKHR/FKHRL-1 (27,46). The immediacy of FKHR/FKHRL-1 activation after seizures suggests that it could account for increased Bim levels and cell death.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings extend work showing that brain injury activates FKHR/FKHRL-1 (27,46). The immediacy of FKHR/FKHRL-1 activation after seizures suggests that it could account for increased Bim levels and cell death.…”
Section: Discussionsupporting
confidence: 85%
“…It has previously been demonstrated that blocking of forkhead dephosphorylation with the nonspecific phosphatase inhibitor SOV reduces hippocampal neuronal death following ischemia (27). To gain insight into whether FKHR/FKHRL-1 activation, and, by inference, Bim, contribute significantly to seizure-induced neuronal death in vivo, we used a similar paradigm to block FKHR/FKHRL-1 dephosphorylation during seizures.…”
Section: Seizure-induced Neuronal Death Is Associated With Upregulatimentioning
confidence: 99%
“…Akt/GSK3b signaling and delayed neuronal cell death H Endo et al ischemia include Bad (Saito et al, 2003), prolinerich Akt substrate (Saito et al, 2004), Forkhead transcription factors (Kawano et al, 2002), and endothelial nitric oxide synthase (Hashiguchi et al, 2004). The current study shows that GSK3b is also one of the targets of Akt in the PI3-K signaling pathway after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed, both Fas ligand and Bim are induced in the ventricular cardiomyocyte after myocardial ischemia/reperfusion-induced injury (18,30). Moreover, we previously documented the FOXOs-mediated increased expression of Fas ligand and Bim in ischemic brain injury in a mouse bilateral common carotid artery occlusion model (61,62,66,67). VO(OPT) treatments prevented ischemia/reperfusion injury-induced expression of Fas ligand and Bim in rat heart (18,19) and brain (51).…”
Section: +mentioning
confidence: 92%
“…We documented that Bad dephosphorylation in the myocardium is associated with decreased Akt activity following myocardial ischemia/reperfusion injury, and VO(OPT)-induced rescue of Akt activity promoted Bad phosphorylation (18). Akt phosphorylates forkhead transcription factors (FOXOs) such as FKHR and FKHRL1 as downstream targets in cell survival signaling (61,62). Phosphorylation of FOXOs reduces their DNA-binding activities, interferes with interactions with other transcription factors, and promotes nuclear export and tethering in the cytoplasm by binding to 14-3-3 proteins (63).…”
Section: +mentioning
confidence: 99%